The management of sales and customer relations (London ; Melbourne : International Thomson Business Press, 1996)
The changing nature of sales and customer relations. Selling and negotiation. Database marketing. Customer service and relationship marketing. Managing agents and distributors. Telemarketing and trade fairs.
Keywords: Management; Sales management; Sales management; Customer relations -- Management